Consequential Effects on Insurance Industry, Risk Management, and Insurability of Pandemic Risk - Saka Toyin Shafau; Abere Omotayo Johncally (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2022)
The continuous fall in the world economy has a result of the COVID19 epidemic attracted the interest of many researchers. The pandemic brought about a sharp decline in the insurance business and the economic growth of the nation; this warranted the closure of many businesses and the insurance businesses is not spared. The objective of this paper is to ascertain the effect of Covid 19 on the insurance business and to determine the most efficient risk management strategies that can coup the effect of the Covid 19 pandemic. Both secondary and primary data were used for this study. A regression model was employed to test the hypotheses raised in this paper. This paper revealed that Covid 19 has a significant negative effect on the business operation of insurance businesses in Nigeria. Arisen from the analysis of the study, the paper recommended that: the insurance industry should employ an effective risk management strategy; there is an urgent need for insurance industries to re-strategies their business operation by introducing new products and services, and insurance companies should introduce attractive prices through price reduction and engage fully the e-marketing system.